Akibat peningkatan tekanan gesek terhadap kekuatan tarik sambungan pada proses pengelasan gesek continuous drive AA6061- baja karbon sedang - Jack Carol Adolf Pah; Defmit B. N. Riwu; Erich U.K. Maliwemu; Adi Yermia Tobe; Wenseslaus Bunganaen; Daud P. Mangesa (TURBO [Tulisan Riset Berbasis Online], 2023)
The objective of this research was to get the effect of friction pressure on the tensile strength of the joining of aluminum alloy AA6061 and carbon steel, with continuous drive friction welding process. Variations of friction pressure of this research were 24 MPa, 32 MPa, and 40 MPa. In this study, a friction time 9 seconds was used. Other friction welding variables were, forging pressure 79 MPa, forging time 60 seconds, and friction rotation speed 1600 rpm. The independent variable was the ultimate tensile strength of the welded joint. The results showed that the increase in the tensile strength of the joint was not linear with the increase of frictional pressure. The rate of the increase in the tensile strength of the connection, will decrease after the frictional pressure passes through 32 MPa. When the rate of increase in the tensile strength of the joint begins to decrease, the joint will become more brittle. The maximum tensile strength of the joint in this study was 167.421 MPa at a frictional pressure of 40 MPa.Rasakan keseruan bermain di om88 dengan peluang menang yang lebih besar. Nikmati pengalaman bermain yang seru, aman, dan penuh tantangan. Segera coba dan raih kemenangan besarmu!